Protocol of a randomised phase III clinical trial of sequential capecitabine or 5-fluorouracil plus bevacizumab (Cape/5-FU-Bmab) to capecitabine or 5-fluorouracil plus oxaliplatin plus bevacizumab (CapeOX/mFOLFOX6-Bmab) versus combination CapeOX/mFOLFOX6-Bmab in advanced colorectal cancer: the C-cubed (C(3)) study - Nagasaka, Takeshi (BMJ Open, 2016)
INTRODUCTION: Results from several randomised trials suggest that the sequential use of cytotoxic agents in patients with metastatic colorectal cancer (mCRC) has the potential to improve overall survival compared with combination chemotherapy. This study is designed to investigate whether sequential treatment with bevacizumab-based first-line treatment with oxaliplatin is superior to combination treatment of mCRC. METHODS AND ANALYSIS: The C-cubed (C(3)) study is a two-arm, multicentre, open-label, randomised phase III trial in Japan comparing the efficacy and safety of sequential capecitabine or 5-fluorouracil plus bevacizumab (Cape/5-FU-Bmab) with escalation to capecitabine or 5-fluorouracil plus oxaliplatin plus bevacizumab (CapeOX/mFOLFOX6-Bmab) versus combination CapeOX/mFOLFOX6-Bmab as the first-line treatment of mCRC. In the sequential arm (Arm A: oxaliplatin ‘wait-and-go’), treatment escalation from Cape/5-FU-Bmab to CapeOX/mFOLFOX6-Bmab is recommended in the case of progressive disease. In the combination arm (Arm B: oxaliplatin ‘stop-and-go’), de-escalation from CapeOX/mFOLFOX6-Bmab to Cape/5-FU-Bmab is possible after 12 weeks of treatment. Re-escalation to CapeOX/mFOLFOX6-Bmab after progressive disease is considered only for patients who received de-escalation of oxaliplatin after 12 weeks of treatment not caused by oxaliplatin-associated toxicity. A target sample size of 304 evaluable patients is considered sufficient to validate an expected HR for time to failure of strategy of the sequential approach ‘wait-and-go’ compared to the combination approach ‘stop-and go’ with 80% power and 2-sided 5% α in case of a true HR<0.69. ETHICS AND DISSEMINATION: This study is conducted according to the standards of Good Clinical Practice and in compliance with the Declaration of Helsinki 2013 and local regulations, and has been submitted and approved by the Ethical Committee of the Non-Profit Organization MINS Institutional Review Board. The protocol and the trial results, even inconclusive, will be presented at international oncology congresses and published in peer-reviewed journals. TRIAL REGISTRATION NUMBER: UMIN000015405, Pre-results.